Estratégias ESG (Environmental, Social and Governance) e desempenho financeiro em cooperativas de crédito - Borges Filho, João Horácio Costa (2024)
Issues related to sustainability and corporate social responsibility have gained prominence since the end of the Second World War, mainly since the 1960s. In this sense, sustainability is characterized as a concept that has been incorporated into organizations, including cooperatives, having in view of the fact that it correlates with cooperative principles. To this end, this study aims to analyze sustainable ESG practices - “Environmental, Social, Governance” and their influence on the financial performance of credit unions. The sustainable ESG practices of credit unions were determined using an ESG Practices Index (IESG), based on a research instrument with 30 binary questions (yes and no), referring to the ESG dimensions (environmental, social and governance). Financial performance was measured by five financial indicators from the PEARLS System (E1, E3, A4, R7 and R8). In methodological terms, the research is characterized as descriptive research with a quantitative approach. As for the procedures, the research is documentary, as Sustainability Reports issued by the Credit Cooperative Centrals that make up the sample were analyzed. Data collection was carried out in the IF.Data database, from the Central Bank of Brazil, while information to measure corporate performance in ESG was obtained from Sustainability Reports, Management Reports, among others published by the Central Cooperatives Credit and available on their websites. For data analysis, Multiple Linear Regression was used with Panel data. The study sample was made up of the 32 credit union Centers in operation in 2022, and in the period from 2018 to 2022, 166 Sustainability Reports and GRSAC Reports were analyzed by the Centers. The research results indicate an evolution in ESG indexes, with 2022 being 60%, in 2021 it was 54%, in 2020 it was 43%, in 2019 it was 38% and in 2018 it was 33%. When analyzing the relationship between ESG performance and the financial performance of Credit Union Centers, it was found that financial performance is positively associated with the Asset Quality (A4) and Effective Financial Structure (E3) indicators and proved to be statistically significant. . The results of this study contribute to a deeper understanding of the influences of ESG practices on the financial performance of credit unions. The study provides relevant information for managers, regulators and accounting scholars, allowing an accurate assessment of the financial performance and sustainability of these Brazilian credit cooperatives in a context marked by an increasing focus on social and environmental responsibility.